勃起功能障碍和其它适应症的治疗 (2024)
本发明大体涉及多种化合物的透皮递送。在一些方面中，透皮递送可通过使用不利的生物物理环境促进。一组实施方案提供用于局部递送的组合物，其包含5型磷酸二酯酶抑制剂和/或其盐，和任选地，不利的生物物理环境和/或一氧化氮供体。在一些情况中，该组合物可使用稳定化聚合物(如黄原胶、#imgabs0#BT和/或#imgabs1#RD)、丙二醇和聚山梨酯表面活性剂如聚山梨酯20加以稳定，与缺少这些物质的一种或多种的组合物相比，这些物质的组合出乎意料的为该组合物提供了温度稳定性，例如，在升高的温度下如至少40℃(至少约104℉)。 The present invention generally relates to a composition for use in a method of treating sexual dysfunction in a subject, preferably a human subject, the composition comprising: an ionic salt present at a concentration of at least about 5% by weight of the composition; xanthan gum; propylene glycol; a polysorbate surfactant; sildenafil and/or a salt thereof; and, a nitric oxide donor comprising L-arginine, an L-arginine salt, and/or L-arginine HCl.